Renal expression and urinary excretion of Na-K-2Cl cotransporter in obstructive nephropathy - Brandoni, Anabel (2017)
Fil: Fil: Brandoni, Anabel. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET); Argentina.